Painting process improvement for automotive industry - Muhammad Farid, M Fathil (2008)
Painting process is an important process in automotive industry. The purposes of the process are to give more attractive appearance to the vehicles and to provide the layer of protection against corrosion and weathering. The painting process are include a few other process, which are Pre-Treatment and Electrodeposition (ED) Process, ED sanding, process, sealant and PVC process, primer process, and top coat process. The objective of the project are to identify the problems occur in ED sanding process and reduce the problems to improve the ED sanding. The study was done at AMM plant in Pekan, Pahang. The methods used to identify the problems are based on the four M method, which are Manpower, Machine, Method, and Materials. The study implement total quality management tools to analysis the problems. From the study that have done, the major problems are the foreign material and the scratch. The foreign material can be reduced by making the solvent so that the layer of anti-corrosion can be eliminate. Meanwhile, the scratch is cause by manpower. The lesss the worker touch the vehicle body, the less scratch formed on the vehicle surface body.